Efeito do treinamento de força com diferentes amplitudes de movimento no torque máximo isométrico em diferentes ângulos articulares - Marina Gurgel Simões (2020)
The range of motion (ROM) manipulation can influence the performance of maximum isometric torque. Thus, the present study aims to compare the change in performance in the maximum voluntary isometric contraction test (MVC) at different joint angles between and within groups performed in different ROM after 12 weeks of knee extensors training. For this, 32 sedentary women between 18 and 30 years old were distributed equally between a control group and three training groups. The volunteers in the training groups performed training protocols 3 times a week consisting of 3-6 sets of 7 repetitions at 60% of the performance in the test of a maximum repetition (1RM), with duration of the repetition of 4s and pause 180s. The only difference between the training protocols was the ROM covered. The first group covered an initial partial range of motion (API) delimited by angles 100º and 65º of knee flexion (0° = extended knee). The second group covered a final partial range of motion (APF) delimited by angles 65º and 30º of knee flexion, The third group covered the complete range of motion (ACO) delimited by angles 100º and 30º of knee flexion. Before and after starting training, MVC tests were performed at angles of 30°, 65° and 100° of knee flexion and relative change in the convenient performance was used for comparison between the groups. The results of the comparison in each angle showed that the groups ACO, API and APF independent the greatest change in performance in the MVC test at the angles of 100° and 65°. In addition, the API group presented a greater relative change than the ACO and APF groups at an angle of 100°. At the 30° angle, only the APF group presented a greater relative change compared to the other groups (ACO, API and Control). Additionally, when comparing angles within each group, the API and APF groups showed an increase in the maximum isometric torque specific to the trained angles and the ACO groups and the Control group showed no differences in the variation of performance in the MVC tests between the investigated angles. In general, an increase in maximum isometric torque consistent with the trained ROM was observed, regardless of whether they were partial or complete ROM.